Performance Analysis of Routing Protocols in Mobile Ad Hoc Networks (MANETs) - Manwal, Manika (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Mobile devices are able to build their own networks, which are referred to as mobile ad hoc networks. These networks do not require any kind of permanent wiring or other infrastructure (MANETs). The success of MANETs and their adaptability to a variety of tasks is, to a considerable extent, based on the routing protocols that they use. Using metrics such as routing overhead, end-to-end delay, and packet delivery ratio, we compare and contrast the various routing protocols that can be employed in MANETs, including proactive, reactive, and hybrid protocols. This comparison and contrast is carried out in this study. In addition to this, we discuss the simulation tools that are utilized to evaluate the efficacy of MANET routing algorithms and define the several performance indicators that may be utilizedin the course of this endeavor. This paper makes a contribution to an ongoing body of research into the analysis of routing protocols in MANETs by offering guidance to network engineers and researchers on how to select the most appropriate routing protocol and simulation tool for a particular MANET scenario. In doing so, the paper maximizes the potential for effective and efficient communication between mobile nodes, which is one of the main goals of the research.